2015
DOI: 10.1002/sd.1592
|View full text |Cite
|
Sign up to set email alerts
|

Green Marketing for Sustainable Development: an Industry Perspective

Abstract: This paper investigates and compares acceptability, perceptions, initiatives and obstacles perceived by public and private manufacturing concerns in India in respect of green marketing. The sample of companies was selected from Delhi and north-western region of India. The study reveals that both public-sector and private-sector companies are concerned for environment and believe that green marketing is relevant for sustainable development. It is also perceived as a promotional tool to build customer trust. Obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 39 publications
(42 reference statements)
1
56
0
9
Order By: Relevance
“…It is important that the language used is functional for the target audience, which describes the data collection criteria and the state of the environment with respect to the parameters influenced by the activity. Business environment communication can be traced back to three types of messages (Garg, 2015):…”
Section: Environmental Business Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important that the language used is functional for the target audience, which describes the data collection criteria and the state of the environment with respect to the parameters influenced by the activity. Business environment communication can be traced back to three types of messages (Garg, 2015):…”
Section: Environmental Business Communicationmentioning
confidence: 99%
“…Conventional strategies have led companies to add various wording to labels such as 'degradable' or 'does not harm the ozone layer' without paying attention to real implications in terms of development and communication. Taking advantage of the opportunities of 'environmental consumerism' requires a more structured commitment, as it is an attempt to protect oneself and the entire planet by purchasing only ecological products (Garg, 2015;Lanfranchi, Giannetto and De Pascale, 2014a).…”
mentioning
confidence: 99%
“…Inicialmente, é relevante destacar que o termo marketing verde (green marketing) tem sido usado de forma intercambiável com outros termos como: marketing ambiental, marketing sustentável, ecomarketing, marketing ecológico, enviropreneurial marketing e marketing de estilos de vida sustentáveis (GARG, 2015;RILEY, 2012). Nessa pesquisa, esses termos também são utilizados de forma intercambiável.…”
Section: Marketing Verde -Conceitos E Delimitaçõesunclassified
“…Para tanto, esses atores precisam reaprender a lidar com essa nova realidade: ter consciência ecológica e assumir as responsabilidades com o meio ambiente, ou seja, precisam se adequar à dicotomia do atendimento aos seus desejos ilimitados com recursos limitados (GARG, 2015;POLONSKY, 1994;.…”
Section: Marketing Verde -Conceitos E Delimitaçõesunclassified
“…Research has suggested that green marketing could indeed contribute to sustainable development even in developing countries (Garg, 2015).…”
Section: Linking Green Marketing and Sustainable Development: A Theormentioning
confidence: 99%